Toxicity and Binding Profile of Lectins from the Genus Canavalia on Brine Shrimp. (27th November 2013) - Arruda, Francisco Vassiliepe Sousa; Melo, Arthur Alves; Vasconcelos, Mayron Alves; Carneiro, Romulo Farias; Barroso-Neto, Ito Liberato; Silva, Suzete Roberta; Pereira-Junior, Francisco Nascimento; Nagano, Celso Shiniti; Nascimento, Kyria Santiago; Teixeira, Edson Holanda; Saker-Sampaio, Silvana; Sousa Cavada, Benildo; et al.
Abstract : Lectins are sugar-binding proteins widely distributed in nature with many biological functions. Although many lectins have a remarkable biotechnological potential, some of them can be cytotoxic. Thus, the aim of this study was to assess the toxicity of five lectins, purified from seeds of different species of Canavalia genus. In order to determine the toxicity, assays with Artemia nauplii were performed. In addition, a fluorescence assay was carried out to evaluate the binding of lectins to Artemia nauplii. In order to verify the relationship between the structure of lectins and their cytotoxic effect, structural analysis was carried out to evaluate the volume of the carbohydrate recognition domain (CRD) of each lectin. The results showed that all lectins exhibited different toxicities and bound to a similar area in the digestive tract of Artemia nauplii. Concerning the structural analysis, differences in spatial arrangement and volume of CRD may explain the variation of the toxicity exhibited by each lectin. To this date, this is the first study that establishes a link between toxicity and structure of CRD from Diocleinae lectins.